Greening Construction Transport as a Sustainability Enabler for New Zealand: A Research Framework - Dhawan, Kamal; Tookey, John E.; GhaffarianHoseini, Ali; GhaffarianHoseini, Amirhosein (Frontiers in Built Environment, 2022)
The construction industry’s inherent fragmentation fuels Construction Supply Chain (CSC) complexity. Logistics form an essential part of the CSC in terms of costs and project management. In turn, transportation accounts for more than half the logistics costs due to construction materials being low-cost/high-volume, and most other logistics processes being business processes and not physical ones. Construction transport is almost entirely road bound, one of the least sustainable modes with externalities far out of proportion to its numbers. Ergo, its optimisation presents substantial greening (de-carbonisation) opportunity, with potentially far-reaching sustainability impacts. The ASI (Avoid-Shift-Improve) concept considers activity, modal structure, and energy intensity/efficiency as transport carbon components, providing a fundamental optimisation framework. 93% of New Zealand’s freight (a third of it construction related) is road bound, with 99% fossil-fuel (diesel) dependence. Government adoption of ASI elements viz Supply Chain (SC) efficiency, transport optimisation, data/information sharing, and collaboration for transport decarbonisation aligns with Industry 5.0, but seeks further research for concrete implementation pathways. This paper aims to bridge the gap by proposing a research framework for greening of construction transport as a sustainability enabler for New Zealand.